Under the Volcano Balanchine & the Kirov - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2005)
The Kirov Ballet dance Balanchine. PALABRAS CLAVE: Kirov Ballet, George Balanchine, Prodigal Son.